Antiplasmodial Activity of Probiotic Limosilactobacillus fermentum YZ01 in Plasmodium berghei ANKA Infected BALB/c Mice - Timothy Bamgbose; Afshana Quadri; Isa O. Abdullahi; Helen I. Inabo; Mohammed Bello; Lokesh D. Kori; Anupkumar R. Anvikar; José de la Fuente; Elianne Piloto-Sardiñas; Alejandro Cabezas-Cruz (Journal of Tropical Medicine)
Malaria remains a significant global health challenge, with the deadliest infections caused by Plasmodium falciparum. In light of the escalating drug resistance and the limited effectiveness of available vaccines, innovative treatment approaches are urgently needed. This study explores the potential of the probiotic Limosilactobacillus fermentum YZ01, isolated from traditionally fermented kindirmo milk, to modify host responses to Plasmodium berghei ANKA infection. Twenty-five male BALB/c mice were grouped and administered various treatments, including probiotic-enriched yogurt alone or in combination with antibiotics. Parameters assessed included gut lactic acid bacteria (LAB) composition, parasitaemia progression, survival rates, and immune response dynamics over a 21-day postinfection period. The probiotic treatment significantly altered gut microbiota, evidenced by increased LAB counts and modulated immune responses, notably enhancing IgM and IL-4 production while reducing IFN-γ levels. Mice receiving prolonged probiotic treatment exhibited delayed parasitaemia onset, reduced mortality rates, and a more robust immune response compared to control groups. These outcomes suggest that probiotic intervention not only tempers the pathological effects of malaria but also enhances host resilience against infection. This study underscores the role of gut microbiota in infectious disease pathogenesis and supports probiotics as a promising adjunct therapy for malaria management.